2014
DOI: 10.3855/jidc.3430
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of extended-spectrum beta-lactamases in human and bovine isolates of Escherichia coli from Oyo state, Nigeria

Abstract: Introduction: The main objective of the study was the molecular characterization of extended spectrum β-lactamases (ESBL) in Escherichia coli isolates collected from human and bovine samples in Oyo state, Nigeria. Methodology: Between August 2010-2011, 114 E. coli isolates were collected from hospitals (n = 57) and bovine (n = 57). PCR and sequencing were used for identification of ESBLs, upstream sequences, plasmid-mediated quinolone resistance (PMQR) genes and class 1 integrons. Plasmid incompatibility group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 19 publications
3
31
4
Order By: Relevance
“…This prevalence rate was slightly higher than a study in Switzerland which reported 8.4% among calves in a slaughter house, but in contrast to a study in South-West Nigeria which reported an absence of ESBL genes among isolates from bovine fecal specimens from slaughter houses (Reist et al, 2013;Inwezerua et al, 2014). The observation shows that the prevalence of ESBL producers in animals is on the rise and may pose risk to humans (Chantziaras et al, 2014).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This prevalence rate was slightly higher than a study in Switzerland which reported 8.4% among calves in a slaughter house, but in contrast to a study in South-West Nigeria which reported an absence of ESBL genes among isolates from bovine fecal specimens from slaughter houses (Reist et al, 2013;Inwezerua et al, 2014). The observation shows that the prevalence of ESBL producers in animals is on the rise and may pose risk to humans (Chantziaras et al, 2014).…”
Section: Discussioncontrasting
confidence: 54%
“…In Nigeria, a previous study in Ibadan, South-Western Nigeria, detected no ESBL-producing isolate in the feces of healthy cattle (Inwezerua et al, 2014). ESBL-producing isolates have however been isolated from pigs (24.2%) and chicken…”
Section: Introductionmentioning
confidence: 99%
“…E. coli ST131 virulenceassociated clonal group was detected in the present study with similar MDR patterns, suggesting the possibility of clonal spread of these MDR E. coli. The presence of E. coli ST131 isolates in West Africa was reported by Aibinu et al [21] from hospital infections in Lagos, while one other E. coli ST131 was identified from a study of inpatients from Oyo State, Nigeria [36]. In a report from another African country, approximately 45% of extended-spectrum β-lactamase (ESBL)-producing E. coli isolates were ST131, which suggested a high rate of virulence-associated E. coli in circulation in Cape Town [75].…”
Section: Discussionmentioning
confidence: 87%
“…Earlier studies from clinical samples on antimicrobial resistance profiles of E. coli from Nigeria recorded a high prevalence to commonly administered antibiotics such as amoxicillin, amoxicillin-clavulanic acid, tetracycline, erythromycin, and trimethoprim/sulfamethoxazole [32][33][34][35]. However, few studies have assessed the antimicrobial and MDR profile of E. coli from community isolates in West Africa [36,37]. Most available data are specific to pathogenic E. coli isolates [13,38].…”
Section: Discussionmentioning
confidence: 99%
“…No single report regarding the presence of ESBL-resistant enterobacteria in companion animals in Nigeria, exist in the literature whereas most Nigerian households keep dogs as pets, guard and/or hunting dogs. Reports in the literature which assessed animals as reservoirs of ESBL-resistant organisms in Nigeria, were those from food animals (Chah and Oboegbulem, 2007;Eze et al, 2013;Duru et al, 2013;Inwezerua et al, 2014;Olowe et al, 2015;Torres et al, 2015). This may paint a picture that only food animals are reservoirs of ESBL-resistant organisms in Nigeria.…”
Section: Introductionmentioning
confidence: 99%